Event-related potential N100 Vs. N170 wave results comparison on driving alertness - Mohamed Aminuddin, Mai Mariam; Mohd Nasir, Haslinah; Brahin, Noor Mohd Ariff; Mustaffa, Izadora (Taylor’s University, 2019)
Driver’s attention, especially during long rides, is very crucial to avoid road accidents, which may lead to injuries and fatalities on the roadway. However, with modern technologies, the decline in driver’s attention can be investigated through the electrical activity of the brain. Event-Related Potential (ERP) is the electrophysiological brain response measurement that related to the sensory, cognitive and motor events. By using simple averaging techniques, ERPs can give reliable result to measure the attentiveness of the driver during driving. In this paper, N100 and N170 wave results were presented, which obtained from temporal and occipital lobes respectively and been compared to measure the driver’s attention. In term of attentiveness difference percentage, it is 0.09% and 38% differences were observed from N100 and N170 wave results respectively. From the results, it clearly can be seen that using N170 wave from occipital lobe is more significant to measure the driver’s alertness compared to N100 wave that recorded from the temporal lobe.